VIDEO BEKAL MAKAN TRANDING, UPAYA MENGURANGI ANGKA STUNTING - Apriliani, Silvi; Sianturi, Risbon; Mulyana, Edi Hendri; Qonita, Qonita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
Abstract Stunting is a condition where children lack proper nutrition and nutritional intake. Lack of understanding from various parties causes high levels of stunting, even from the smallest scope, namely parents who do not provide quality nutrition which is considered very fatal. Video creations for school lunches which have been trending recently are an answer to overcome this problem. This qualitative study aims to find out how effective the trending school lunch video is in having a good impact on the understanding of parents and teachers in providing quality and interesting food supplies, of course. This research compares two schools, which implement the provision of bergzi school meals, with schools that do not implement this process due to a lack of information or digital literacy regarding circulating videos. The collected data was analyzed using the